Pengaruh Disiplin Kerja, Kepuasan Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Divisi Konstruksi Pada PT Telkom Akses Yogyakarta - Inayat Hanum Indriati; Ratnaningrum, Natalia; Kharisma Putri, Soraya (Universitas PGRI Yogyakarta, 2024)
This research aims to determine the influence of work discipline, job satisfaction, and work environment on performance.This research was conducted in December 2022- December 2023 in the construction division of PT Telkom Access Yogyakarta. This research is quantitative research with a total of 60 employees as respondents and the sampling technique uses saturated samples. Data collection techniques were carried out by means of interviews and questionnaires. The data analysis technique used is multiple linear regression analysis with the help of SPSS 25.0 for windows. The results of this research show that partially work discipline has a positive and significant effect on performance with a regression coefficient of 0.379 and sig 0.003 <0.05. Job satisfaction has a positive and significant effect on performance with a regression coefficient of 0.250 and sig 0.020 <0.05. The work environment has a positive and significant effect on performance with a regression coefficient of 0.126 and sig 0.016 <0.05. Simultaneous test results (F test) show that work discipline, job satisfaction and work environment have a significant effect on performance, as evidenced by the F value of 13.395 and sig 0.000 < 0.05. The influence of work discipline, job satisfaction and work environment is shown by the Adjusted R Square value of 0.387, the remaining 0.613 is influenced by other variables not examined in this research.